Determinants of customer satisfaction of banking industry in Bangladesh - Mohammed Belal Uddin; Bilkis Akhter (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
This study aims to investigate, through the development and operationalized constructs of service quality, service charge, perceived value, and customer satisfaction; customer satisfaction and its determinants of the banking industry in Bangladesh. An exploratory factor analysis and structural equation modeling was used to analyze data. Measurement model and structural model indicate that service quality and fair service charge both have positive direct impact on customer satisfaction in a mass service industry (i.e., banking industry). It was further observed that they also have indirect influence on customer satisfaction through perceive value, i.e. perceived value has mediating role between quality, charge fairness and satisfaction. Bank managers are recommended to formulate operations and marketing strategies that focus on desires of customers to enhance level of satisfaction.
Keywords: 330; Service quality; Service charge; Perceived value; Customer satisfaction; Banking industry; Bankgeschäft; Kundenzufriedenheit; Dienstleistungsqualität; Bangladesch